2007
DOI: 10.1007/s10666-007-9108-4
|View full text |Cite
|
Sign up to set email alerts
|

Emission Factors Determination of Euro III 1,200- to 1,400-cc Petrol Passenger Cars with a PLS Multivariate Regression Model

Abstract: This paper presents emission factors of a class of passenger cars obtained by applying a statistical model developed to evaluate average emission factors based on driving cycle emission measurements. A multivariate regression method based on principal components, namely, the partial least squares (PLS) method, is applied to calculate the model. The method was applied to emission data from a sample of petrol Euro III 1,200-to 1,400-cc passenger cars taken from the ARTEMIS database. A vehicle effect analysis sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…CMEM (Scora and Barth, 2006). Detailed information on vehicle state and emission is therefore required to determine model forms and to estimate model parameters (Rapone et al, 2008). …”
Section: Emission Estimation Modelsmentioning
confidence: 99%
“…CMEM (Scora and Barth, 2006). Detailed information on vehicle state and emission is therefore required to determine model forms and to estimate model parameters (Rapone et al, 2008). …”
Section: Emission Estimation Modelsmentioning
confidence: 99%
“…The model is able to calculate emission factor [15] taking into account a large number of parameters to characterize the kinematics of DCs. In the emission modelling context the dimensionality consideration could be probed by PLS (Partial Least Squares) multivariate regression method.…”
Section: Modelling Approachmentioning
confidence: 99%
“…Following previous studies [15,16] two blocks of X variables were identified considering two potential causes of variability in emissions for a driving cycle: energy expenditure from the vehicle in the cycle and the acceleration events at different speeds.…”
Section: Modelling Approachmentioning
confidence: 99%
“…According to a multi-block approach (MBPLS) [5], a base model 1 is defined for block1 and a base model 2 is calculated for block2 of variables. Then the super block regression model, named top model, is built, making the regression of Y-variables on the union of scores of the two base models.…”
Section: The Core Of Is: the Model Basementioning
confidence: 99%
“…The latest version is 2.1 and dates from February 2004, in which the emission factors of the HDV (heavy duty vehicles) are completely revised and new measurements for all vehicle categories up to EURO3 are included. The kinematic model approach in ARTEMIS was developed by Rapone [5], and it predicts average emissions on a microtrip (driving pattern) obtaining a detailed description of the velocity profile using a multidimensional approach. This kinematic model (Kinematic Emission Model KEM) is defined as a meso-scale emission model, and it is to be pointed out that it may require less detailed information with respect to instantaneous models.…”
Section: Introductionmentioning
confidence: 99%